2013
DOI: 10.1371/journal.pone.0070761
|View full text |Cite
|
Sign up to set email alerts
|

Relating Lateralization of Eye Use to Body Motion in the Avoidance Behavior of the Chameleon (Chamaeleo chameleon)

Abstract: Lateralization is mostly analyzed for single traits, but seldom for two or more traits while performing a given task (e.g. object manipulation). We examined lateralization in eye use and in body motion that co-occur during avoidance behaviour of the common chameleon, Chamaeleo chameleon. A chameleon facing a moving threat smoothly repositions its body on the side of its perch distal to the threat, to minimize its visual exposure. We previously demonstrated that during the response (i) eye use and body motion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Even with different individuals, the number of significant responses to the left side was always prevalent in each of the three simulated antipredatory situations. Moreover, some of the tested individuals showed a consistent response in different experiments, suggesting a possible spontaneous tendency to not escape randomly from a predator, but to select a preferential side for escape, as found in other taxa (Bonati et al, 2010;García-Muñoz et al, 2012;Lustig et al, 2013b). Many studies have shown evidence of a left-lateralized hemisphere in contexts requiring focused attention for controlling feeding cues and searching for food resources, by using the right eye (Rogers, 1997;Robins, 2006;Bonati et al, 2008;Lippolis et al, 2009).…”
Section: Discussionmentioning
confidence: 64%
“…Even with different individuals, the number of significant responses to the left side was always prevalent in each of the three simulated antipredatory situations. Moreover, some of the tested individuals showed a consistent response in different experiments, suggesting a possible spontaneous tendency to not escape randomly from a predator, but to select a preferential side for escape, as found in other taxa (Bonati et al, 2010;García-Muñoz et al, 2012;Lustig et al, 2013b). Many studies have shown evidence of a left-lateralized hemisphere in contexts requiring focused attention for controlling feeding cues and searching for food resources, by using the right eye (Rogers, 1997;Robins, 2006;Bonati et al, 2008;Lippolis et al, 2009).…”
Section: Discussionmentioning
confidence: 64%
“…The prehensile tail serves as a fifth limb for balancing and stabilizing while grasping trees. The reptile is an omnivore, which means it eats insects as well as fruits and vegetables (Eid et al, 2011;Gillette & Krysko, 2012;Lustig et al, 2013;Melero Jurado, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Males have a larger body (17-24 inches) and casque (head crest or helmet) when mature. The lifespan of a veiled chameleon is usually eight years for males and five years for females (Lustig et al, 2013). Veiled chameleons reach sexual maturity at 4-5 months (Bartlett & Bartlett, 1995).…”
Section: Introductionmentioning
confidence: 99%